Fertility Issues among Young Cancer Survivors: A Systematic Review - Seyede Zahra Ghaemi; Abozar Javadipour; Seyed Taghi Heydari; Zohreh Abasi (Mashhad University of Medical Sciences, 2021)
Background & aim: Fertility issues after cancer have recently received great attention. This study was designed to review the impacts of breast cancer treatment on fertility. Methods: This study is a narrative review. Textbooks as well as electronic databases including ProQuest, Google Scholar, PubMed, Scopus, Web of Science, Science Direct, and MEDLINE were comprehensively searched for scientific literature. The search strategy was based on keywords: "Fertility", "Childbearing", "Breast Cancer Survivorship", "Reproductive Issues". A total of 270 titles and abstracts were recognized through searching. Studies, which focused on medical or biological consequences and included premenopausal women or subjects younger than 50 years, were eligible for review. After removing duplicates, studies focused on patients who were not in their reproductive age, and studies with stereotyped results, 30 articles met the inclusion criteria. The articles were screened with regard to their titles and types. The abstracts which best fitted the inclusion criteria were checked for eligibility, and then their full texts were read. To guarantee the consistency of the retrieved information, the data was independently extracted from each study by all the authors, and then was entered to the standardized tables. Results: Long-term fertility dysfunctions happen in most patients under cancer treatment. Also, breast cancer survivors of the reproductive age suffered greater distress over cancer-related infertility. Conclusion: Counseling methods to obtain information about the risk of treatment on fertility and ways to preserve fertility should be presented early in the treatment.